2019
DOI: 10.1103/physreva.99.042507
|View full text |Cite
|
Sign up to set email alerts
|

Microwave spectroscopy of the Yb 6s(n+3)d6sng , 6snh

Abstract: Using a microwave and radio frequency resonance approach we observe the transitions of ytterbium from the 6s(n + 3)d states to the 6snℓ states for 4 ≤ ℓ ≤ 6 and 28 ≤ n ≤ 33. The energies of the 6snℓ states of ℓ ≥ 4 are determined from the observed intervals and the known values of the 6snd energies. We use a non-adiabatic core polarization model to analyze the energy levels to determine the dipole (α d ) and quadrupole (α q ) polarizabilities of the ground state of Yb + . We find the values α d = 60.51(10) a 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[29] Recently, using microwave and radio frequency resonance methods, Niyaz et al observed the transition of ytterbium from 6s(n + 3)d 1 D 2 → 6snl, 4 ≤ l ≤ 6. [30] Besides experimental observations, many groups have developed new theoretical methods to calculate the structural parameters of Yb atoms. Ternovsky et al [31] applied the method of relativistic many-body perturbation and the Dirac-Kohn-Sham zeroth approximation combined with the generalized relativistic energy method , and calculated the energy and width of the self-ionizing resonance of 4f 14 7s6p, 4f 13 [ 2 F 7/2 ]6s 2 np[5/2] 2 , 4f 13 [ 7 F 7/2 ]6s 2 nf[5/2] 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[29] Recently, using microwave and radio frequency resonance methods, Niyaz et al observed the transition of ytterbium from 6s(n + 3)d 1 D 2 → 6snl, 4 ≤ l ≤ 6. [30] Besides experimental observations, many groups have developed new theoretical methods to calculate the structural parameters of Yb atoms. Ternovsky et al [31] applied the method of relativistic many-body perturbation and the Dirac-Kohn-Sham zeroth approximation combined with the generalized relativistic energy method , and calculated the energy and width of the self-ionizing resonance of 4f 14 7s6p, 4f 13 [ 2 F 7/2 ]6s 2 np[5/2] 2 , 4f 13 [ 7 F 7/2 ]6s 2 nf[5/2] 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this limit, it is mandatory to increase the angular momentum of the Rydberg electron [13]. Up to now, moderately largestates have been produced using microwave transfer [23] or Stark switching methods [24][25][26][27]. These early studies have evidenced the reduction of the autoionization rate with but extending their techniques to > 10 is challenging [28].…”
mentioning
confidence: 99%